Elite and sub-elite youth soccer players show no difference in vertical jump performance - Kalata, M.; Varjan, M.; Hank, M.; Mala, L.; Imal, O.; Marketin, J. (SportMont, 2023)
This study aimed to determine whether vertical jump performance differs among youth players with different performance levels. A total of 84 youth male soccer players from the U19 category were recruited. The players were divided into the elite (EG) and sub-elite (SEG) groups based on their performance level. The vertical jump (VJ) performance during countermovement jump with free arms (CMJFA) and drop jump (DJ) were measured using two force platforms Kistler B8611A at a sampling rate of 1000 Hz (KISTLER Instrumente AG, Switzerland). The following outcome variables were calculated in all participants: vertical jump height (VJH), vertical ground reaction force (VGRF), and force impulse (FI) in absolute and relative values. Data analysis showed no significant differences (p>0.05) with trivial to small effects in VJH for both jump types (CMJFA and DJ) between EG and SEG. FIrelative provides a good indication of VJH in comparison with the other kinematic variables selected in this study. The leg muscle mass (LMM) ratio normalised to body mass provides a better association with VJH than the other selected morphological variables in this study, although a small effect size was observed. VJH does not appear to be a distinguishing feature among soccer players in the first two performance levels in the U19 category. Therefore, the results may not be sensitive enough to differentiate the performance levels, especially when the difference is only in one performance level. Future research should consider using other parameters, such as the eccentric rate of force development or reactive strength index, as recommended in a previous study.